Causes and clinical outcomes of pregnancy-related acute kidney injury: A single-center tertiary hospital study in Abu Dhabi, United Arab Emirates - Hefsa Al Shamsi; Salama Al Falahi; Bashir Taha; Salema Wani; Fatma Farooq (Saudi Journal of Kidney Diseases and Transplantation, 2026)
Abstract Background: Pregnancy-related acute kidney injury (prAKI) remains a serious complication associated with maternal and fetal morbidity, with significant regional variation. Data from the Middle east are limited. This study aimed to investigate the causes and outcomes of prAKI in a tertiary hospital in Abu Dhabi. Methods: We conducted a retrospective cohort study of pregnant women with prAKI at Corniche Hospital, Abu Dhabi, between 2019 and2023. AKI was defined according to the Kidney Disease Improving Global Outcomes (KDIGO) criteria as any of the following ≥ 1.5-fold increase in serum creatinine from the baseline within 7 day or ≥ 0.3mg/dl (≥26.5 μmol/L) increase from the baseline within 48 hours. Baseline serum creatinine was defined as the most recent creatinine value within 1 year prior to the index pregnancy. In cases where baseline creatinine was not available, the lowest serum creatinine value recorded after recovery was used as a surrogate baseline. Complete renal recovery is return to baseline serum creatinine and partial recovery if the creatinine did not return to baseline. Results: A total of 167 patients had prAKI over a 5-year study period. The most common cause of prAKI was preeclampsia, accounting for 65 cases (39%), followed by infection 30 cases (18%) of the cases. The majority of cases were classified as mild acute kidney injury (AKI) (75.5%), while moderate and severe AKI accounted for 16% and 8%, respectively. Maternal outcomes were generally favorable, with a low mortality rate (0.6%). Complete renal recovery was observed in 148 patients (88.6%), eight patients progressed to chronic kidney disease, while follow up serum creatinine was not done in 11 patients (6.6%). Only two patients required transient renal replacement therapy. prAKI was recognized and documented by the obstetric team in 60% of the cases. Conclusion: In this cohort, prAKI was predominantly mild and associated with favorable maternal outcomes, likely reflecting early detection and management in a tertiary care hospital. However, under-recognition of prAKI remains a concern. Multidisciplinary collaboration between obstetric and nephrology teams is key for prevention, early recognition and management of AKI.